Methodology and Rationale for Ophthalmic Examinations in the Seventh and Eighth Korea National Health and Nutrition Examination Surveys (2017–2021) - Song, Su Jeong; Choi, Kyung Seek; Han, Jong Chul; Jee, Donghyun; Jeoung, Jin Wook; Jo, Young Joon; Kim, Jae Yong; Kim, Ko Eun; Kim, Seong Taeck; Lee, Ji Woong; Lee, Tae Eun; Lim, Dong Hui; et al. (Korean journal of ophthalmology, 2021)
This report provides a detailed description of the methodology for ophthalmic examinations according to the Korea National Health and Nutrition Examination Survey (KNHANES) VII and VIII (from 2017 to 2021). The KNHANES is a nationwide survey which has been performed since 1998 in representatives of whole Korean population. During the KNHANES VII and VIII, in addition to the ophthalmic questionnaire, intraocular pressure measurement, visual field test, auto refractometry, axial length and optical coherence tomography measurements were included. This new survey will provide not only provide normative and pathologic ophthalmic data including intraocular pressure, refractive error, axial length, visual field and precise measurement of anterior segment, macula and optic nerve with optical coherence tomography, but also a more accurate diagnosis for major adult blindness diseases, including age-related macular degeneration, diabetic retinopathy, glaucoma, and other ocular diseases, for the national Korean population.